Solvent extraction and fluorescence spectroscopic investigation of the selective Am(III) complexation with TS-BTPhen - Kaufholz, Peter; Modolo, Giuseppe; Wilden, Andreas; Sadowski, Fabian; Bosbach, Dirk; Wagner, Christoph; Geist, Andreas; Panak, Petra; Lewis, Frank W.; Harwood, Laurence M. (Solvent extraction and ion exchange, 2016)
An americium(III) selective separation procedure was developed based on the coextraction of trivalent actinides (An(III)) and lanthanides (Ln(III)) by TODGA (N,N,N′,N′-tetraoctyl-diglycolamide), followed by Am(III) selective stripping using the hydrophilic complexing agent TS-BTPhen (3,3′,3ʺ,3ʺ′-[3-(1,10-phenanthroline-2,9-diyl)-1,2,4-triazine-5,5,6,6-tetrayl]tetrabenzenesulfonic acid). Distribution ratios were found at an acidity of 0.65 mol L−1 nitric acid that allowed for the separation of Am(III) from Cm(III) (DCm > 1; DAm < 1), giving a separation factor between curium and americium of SFCm/Am = 3.6 within the stripping step. Furthermore, Am(III) was readily separated from the lanthanides with the lowest selectivity for the Ln(III)/Am(III) separation being lanthanum with a separation factor of SFLa/Am = 20. The influence of the TS-BTPhen concentration on Am(III) distribution ratios was studied, giving a slope (logD vs. log[TS-BTPhen]) of approximately −1 for the stripping of An(III) with TS-BTPhen from the TODGA-based organic phase. Time-resolved laser fluorescence spectroscopy (TRLFS) measurements of curium(III) were used to analyze the speciation of Cm(III)-TS-BTPhen complexes. Both 1:1 and 1:2 complexes were identified in single-phase experiments. The formation of the 1:1 complex was suppressed in 0.5 mol L−1 nitric acid but it was significantly present in HClO4 at pH 3. Conditional stability constants of the complex species were calculated from the TRLFS experiments.